2020
DOI: 10.31875/2409-9848.2020.07.8
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Spot Welding Electrode Material Properties Using AHP

Abstract: An objective of this research is to rank the essential property required for spot welding material selection. Total ten attributes namely Electrical conductivity, Thermal conductivity, Rockwell Hardness, Wear resistance, Density, Cost, Melting point, Percentage Elongation, Yield Strength and Ultimate Tensile Strength were considered for the purpose of selection of the electrode Material. In order to select appropriate spot welding electrode, authors have studied various Copper alloys having equally good proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The authors, Bachchhav et al, used the analytical hierarchy process (AHP) to rank the material properties of spot-welding electrodes. They discovered that high electrical conductivity, thermal conductivity, and wear resistance are the most predominant properties out of the 10 characteristics considered [6]. However, conducting this analysis using a single material presents several challenging obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…The authors, Bachchhav et al, used the analytical hierarchy process (AHP) to rank the material properties of spot-welding electrodes. They discovered that high electrical conductivity, thermal conductivity, and wear resistance are the most predominant properties out of the 10 characteristics considered [6]. However, conducting this analysis using a single material presents several challenging obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…An important attributes were considered based on results obtained through AHP analysis are electrical conductivity (EC) in, thermal conductivity (THC), Rockwell hardness (RH), yield strength (YS), density (D), cost (C), wear resistance (WR). [3] The values of the attributes for the selected materials were collected from open literature and depicted in Table 2. [3,[19][20][21][22] Determining the Weight of W j of the Criteria Let x ij be performance score of i th alternative of j th parameter The relative significance of each criterion is calculated as follows:…”
Section: Determining the Criteriamentioning
confidence: 99%
“…Analytic hierarchy process (AHP) is an effective method of correctly assessing the conflicting data by a pairwise judgment between the attributes under consideration. [1][2][3][4] Attempts have been made to rank spot welding electrode material properties using AHP and found that high electrical conductivity, thermal conductivity and wear resistance are most predominant properties amongst all ten attributes under consideration. [3] AHP were performed for various applications such as critical property assessment novel brake pad material selection [5,6] and grade classification of bio-lubricants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Необходимым условием для осуществления процесса сварки выступает более высокое электросопротивление на границе свариваемых частей изделия в зоне их контакта. выполняют три основные функции: передают давление при сжатии деталей, подводят к ним электрический ток и отводят тепло, выделяющееся в процессе сварки.Среди многочисленных марок бронз[2,3,7], применяемых для изготовления электродов, выделяется группа медных сплавов с малым (0,3-1 %) содержанием легирующих элементов (кад-миевые, хромистоциркониевые, хромистые бронзы)[6]. Эти бронзы обладают близкой электрои теплопроводностью в сравнении с чистой медью.…”
unclassified